2007
DOI: 10.1128/aac.00317-07
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Genetic Diversity in the Plasmodium falciparum Na + /H + Exchanger 1 Transporter Protein Implicated in Quinine Resistance

Abstract: The Plasmodium falciparum Na ؉ /H ؉ exchanger (Pfnhe-1) locus at chromosome 13 and another locus at chromosome 9 have recently been proposed to influence quinine resistance. Here, we sequenced the ms4760 locus of the Pfnhe-1 gene from 244 P. falciparum isolates collected from five different regions of India. A total of 16 different ms4760 alleles (with one to five DNNND repeats) were observed among these isolates. Interestingly, areas with a high prevalence of chloroquine and sulfadoxine-pyrimethamine resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
17
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 15 publications
5
17
0
Order By: Relevance
“…19,22 This situation is likely reflecting the level of malaria transmission, but it also could be related to the prevalence of resistant parasites to quinoline antimalarial drugs. This latter hypothesis is strengthened by our data, which show that isolates from the Comoros (an area with a high prevalence of antimalarial drugs resistance, although specific data about QN resistance are lacking) had significantly more repeats in block II (DNNND) than those isolates from Madagascar (a low drug-resistance area); these findings are consistent with some previous findings observed in culture-adapted parasites from Asia, 13,18,19,21,22 India, 23 and East Africa. 20 In conclusion, current observations from molecular surveys that aimed to define an association between potential contributors to QN resistance, such as ms4760 allele polymorphism, have generated conflicting data and do not allow for proposing a simple molecular typing methodology of global application based on this molecular marker.…”
supporting
confidence: 82%
See 3 more Smart Citations
“…19,22 This situation is likely reflecting the level of malaria transmission, but it also could be related to the prevalence of resistant parasites to quinoline antimalarial drugs. This latter hypothesis is strengthened by our data, which show that isolates from the Comoros (an area with a high prevalence of antimalarial drugs resistance, although specific data about QN resistance are lacking) had significantly more repeats in block II (DNNND) than those isolates from Madagascar (a low drug-resistance area); these findings are consistent with some previous findings observed in culture-adapted parasites from Asia, 13,18,19,21,22 India, 23 and East Africa. 20 In conclusion, current observations from molecular surveys that aimed to define an association between potential contributors to QN resistance, such as ms4760 allele polymorphism, have generated conflicting data and do not allow for proposing a simple molecular typing methodology of global application based on this molecular marker.…”
supporting
confidence: 82%
“…14,15,[17][18][19][20][21][22] However, significant differences in the distribution and prevalence of allele were observed both between countries and within sites in the Comoros ( Table 1). The genetic diversity of the ms4760 allele observed in our study was similar between both countries (0.84 and 0.85), and it was comparable with the genetic diversity previously described in African (Congo = 0.76, Uganda = 0.79, and Kenya = 0.66) 15,17,20 and Indian isolates (0.68) 23 and significantly higher than the diversity found in Asian isolates (China/Myanmar = 0.68, P = 0.04; Vietnam = 0.49, P 0.0001). 19,22 This situation is likely reflecting the level of malaria transmission, but it also could be related to the prevalence of resistant parasites to quinoline antimalarial drugs.…”
supporting
confidence: 75%
See 2 more Smart Citations
“…A seminal study on the association of polymorphisms in pfnhe, a sodium hydrogen exchanger gene, and the in vitro activity of QN indicated that an increase in the number of DNNND repeats (1)(2)(3)(4)(5) in an ms4760 microsatellite was associated with reduced susceptibility to QN (10), and this finding was confirmed recently (13). Variations in the copy number of this repeat in isolates from areas where QN efficacy is known to be reduced in vivo have also been reported (41).…”
supporting
confidence: 53%